Fine-tuning of the dielectric properties of polysiloxanes by chemical modification1. Issue 62 (8th July 2015) - Dünki, Simon J.; Tress, Martin; Kremer, Friedrich; Ko, Song Yee; Nüesch, Frank A.; Varganici, Cristian-Dragos; Racles, Carmen; Opris, Dorina M.
<x xml:space="preserve">Abstract</x> Novel polysiloxanes with dielectric properties which are systematically fine-tuned by utilizing thiol-ene post-polymerization reactions of a polymethylvinylsiloxane with various ratios of 1-butanethiol and 3-mercaptopropionitrile is presented.